An Improved Acquisition Method for GNSS in High Dynamic Environments: Differential Acquisition Based on Compressed Sensing Theory. Issue 1 (March 2017) - Wu, Chao; Xu, Luping; Zhang, Hua; Zhang, Hongyang
Abstract: Due to the influence of bit sign and frequency error on integration peak, the Deterministic Compressed GNSS Acquisition Method (DCGAM) has poor detection performance in high dynamic environments. For fast acquisition in high dynamic environments, this paper has proposed an improved compressed GNSS acquisition method using adjacent part differential coherence. First, the adjacent part differential coherence process between the two neighbor milliseconds is used. This reduces the impact of bit sign and frequency error on the integration amplitude. Then, the decision variable is built when the differential signal goes through the compressed process. The detection probability, false alarm probability, and miss probability are derived to calculate the Mean Acquisition Time (MAT). Finally, the simulation results show that the proposed method has better detection probability and lower MAT than DCGAM under the same false alarm probability. Moreover, the experimental results yield these same results. Copyright © 2017 Institute of Navigation